The role of entomological surveillance in the first urban active focus of Visceral Leishmaniasis in the city of Rio de Janeiro - Rodrigues, Cláudio Manuel (ABCS Health Sciences, 2018)
Introduction: Leishmaniasis, Visceral (LV) is an anthropozoonosis caused by Leishmania infantum that was advanced in the last thirty years in the urban environment. Since 1977 there are records of the disease in peripheral areas of the municipality of Rio de Janeiro, however, in 2011 it was described in the Caju neighborhood by means of the diagnosis of the parasite in infected dogs and the capture of specimens of its main vector. Objective: This article aims to disclose the primary work of entomological capture and identification of these specimens that provided surveillance actions in the first urban active focus of LV in the city of Rio de Janeiro, quoted recently in several studies, but not publicized in all its details. Methods: The adapted CDC light traps were installed in a circular sector of 1000 m radius from the supposed focal point, from 5:00 p.m. to 7:00 p.m. the following morning, between June and September 2011. Results: A total of 253 specimens of Lutzomyia longipalpis were collected, 63.1% of which in the kennel area, considered the primary focus of dispersion of the vectors. Conclusion: The results described corroborate articles indicating the urbanization of the main vector of LV, stressing the importance of more detailed studies of its urban life cycle and the need of the changing paradigms of leishmaniasis surveillance in Brazil.